Some values of the reduction factor for plastic buckling of plates in shear - Emslie, B. (College of Aeronautics, 1959)
In this note values are obtained for the plasticity reduction factor for plates in shear, based on incremental plasticity theory. These values are compared with other theoretical results and with some experimental results.